2011
DOI: 10.5089/9781463922559.001
|View full text |Cite
|
Sign up to set email alerts
|

Does G-4 Liquidity Spill Over?

Abstract: The resumption of strong capital flows into emerging markets in mid-2009 brought back the debate over whether pull or push factors are the main determinants. This paper, using panel specifications with alternative measures of global liquidity, asks the question whether G-4 liquidity expansion spills over to the rest of the world. The paper finds strong positive links between G-4 liquidity expansion and asset prices, such as equities, in the liquidity receiving economies, which indicates that the push factor pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This phenomenon further explains the positive relationship between high interest rate and capital inflows. To explain the relationship between high interest rate and capital inflows, Psalida and Sun () indicate that in mid‐2009, gradual shift in global portfolio allocation towards emerging markets, triggered by liquidity spillover from developed economies, has led to portfolio inflows that for a number of these countries are large in relation to the absorptive capacity of their domestic markets. This liquidity spillover occurred as a number of developed economies adopted expansionary monetary policy to respond to the 2007 global financial crisis.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…This phenomenon further explains the positive relationship between high interest rate and capital inflows. To explain the relationship between high interest rate and capital inflows, Psalida and Sun () indicate that in mid‐2009, gradual shift in global portfolio allocation towards emerging markets, triggered by liquidity spillover from developed economies, has led to portfolio inflows that for a number of these countries are large in relation to the absorptive capacity of their domestic markets. This liquidity spillover occurred as a number of developed economies adopted expansionary monetary policy to respond to the 2007 global financial crisis.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…Previous studies (Brana et al 2012;Belke et al 2010a;Sousa and Zaghini 2007) showed that global liquidity positively influenced short-term output. Psalida and Sun (2011) also observed positive effects on the credit gap, indicating the role of credit channels in the transmission of global liquidity impacts. Meanwhile, Matsumoto (2011) found that the rising levels of global risk aversion, as measured by the CBOE volatility index (VOX index), have a negative effect on output in various developed and emerging countries.…”
Section: Theoretical Backgroundmentioning
confidence: 85%
“…Ruffer and Stracca (2006) find that a positive shock to global excess liquidity (defined as the ratio between broad money to nominal GDP) leads to a significant rise in domestic real output and price level for the euro area and Japan. Additionally, global liquidity has a significant impact on asset and commodity prices (Darius and Radde, 2010, for global house prices; Thomas, Muhleisen and Pant, 2010, for world oil prices;and Psalida and Tao, 2011, for the impact of G4 liquidity expansion on asset prices in the rest of the world).…”
Section: Literature Reviewmentioning
confidence: 99%